Electric vehicle battery secondary use under government subsidy: A closed-loop supply chain perspective - Gu, Xiaoyu; Zhou, Li; Huang, Hongfu; Shi, Xiutian; Ieromonachou, Petros (International journal of production economics, 2021)
Electric vehicle batteries should normally be removed from electric vehicles when their power capacity fall to 70% ~ 80% of new batteries. However, removed batteries can still be secondary used for other purposes, such as energy storage, before remanufacturing. To promote electric vehicle battery secondary use, this research studies a two-period battery secondary use closed-loop supply chain model consisting of a battery (re)manufacturer, a secondary user and a government. The government may provide subsidies for the secondary users to incentivize electric vehicle battery secondary use. It is found that, only when the recycled batteries' remaining power capacity is relatively high or their remanufacturing rate is relatively low, the government will consider a subsidy. In addition, under government's subsidy regulation, secondary battery users need to determine the quantities of batteries with relatively high power capacity for secondary use. Theoretically, this study enriches the research field of sustainable development of electric vehicle battery industry. Practically, this study also helps practitioners to better manage closed-loop supply chains with battery secondary use, and to enhance supply chain efficiency. Also, this study contributes to governments' regulatory decisions toward electric vehicle industries to balance economy and sustainability in society.